Neuro‐Sjögren: Uncommon or underestimated problem?. Issue 8 (25th June 2020) - Jaskólska, Marta; Chylińska, Magdalena; Masiak, Anna; Siemiński, Mariusz; Ziętkiewicz, Marcin; Czuszyńska, Zenobia; Smoleńska, Żaneta; Zdrojewski, Zbigniew
Abstract: Objectives: Sjögren's syndrome (SS) is a chronic inflammatory disease with an autoimmune background with possible complications from peripheral (PNS) and central nervous system (CNS). The aim of this study was to assess the prevalence and to describe the phenotype of peripheral neuropathies in patients with SS. Materials & Methods: We studied fifty patients with primary Sjögren's syndrome for peripheral nervous system involvement. All patients underwent neurological and rheumatological examination followed by nerve conduction studies (NCS) of nine peripheral nerves. Results: Thirty‐six patients (72%) fulfilled the criteria for the diagnosis of neuropathy. Carpal tunnel syndrome (54%) and axonal sensorimotor neuropathy (22%) were the most common. Neurological symptoms preceded the diagnosis of SS in eight patients. Conclusions: Peripheral neuropathies are frequent in SS patients. Neurologists should be aware of possible autoimmune causes of neuropathies because clinical manifestations of neuropathy may precede the development of other symptoms of the autoimmune disease. Abstract : Our study shows that peripheral neuropathies are frequent among patients with primary Sjögren's syndrome. Neurologists should be aware of possible autoimmune causes of neuropathies because clinical manifestations of neuropathy may precede the development of other symptoms of the autoimmune disease.